Differential associations of dietary inflammatory potential, antioxidant capacity, and Mediterranean diet adherence with biological aging: A UK Biobank study - Cong Zhang; Ren-Fang Han; Song Yin; Yue-Qing Huang (The Journal of Nutrition, Health and Aging, 2025)
Background: Biological aging, distinct from chronological age, significantly impacts chronic disease risk and is a crucial target for health interventions. While diet is hypothesized to influence aging through inflammatory and oxidative pathways, systematic evidence from large populations remains limited. To address this gap, we used UK Biobank data with complementary dietary indices assessing inflammatory and antioxidant properties, providing comprehensive insights into diet-aging links. Methods: We analyzed data from 46,755 UK Biobank participants in this cross-sectional study. Dietary inflammatory potential, antioxidant capacity, and Mediterranean diet adherence were assessed using the Dietary Inflammatory Index (DII), Composite Dietary Antioxidant Index (CDAI), and Alternative Mediterranean Diet (aMED) scores, respectively, derived from 24-h food consumption reports. Biological age acceleration was quantified by Klemera-Doubal method biological age (KDM-BA) and phenotypic age (PhenoAge). Multivariate linear and logistic regressions, restricted cubic spline models, and mediation analyses were performed, adjusting for extensive confounders. Results: Pro-inflammatory diets (higher DII scores) were significantly associated with increased biological age acceleration (KDM-BA: β = 0.39; PhenoAge: β = 0.96, all P < 0.001), whereas antioxidant-rich diets (higher CDAI scores) and Mediterranean diets (higher aMED scores) showed inverse associations (CDAI: β= −0.33 to −0.50; aMED: β = −0.31 to −0.60, all P < 0.001). Logistic regressions confirmed that aMED adherence reduced odds of biological age acceleration (OR: 0.68–0.69, P < 0.001). Dose-response analyses revealed nonlinear positive associations between DII and PhenoAge acceleration (Pnonlinear < 0.001), nonlinear negative associations for CDAI (Pnonlinear ≤ 0.016), and near-linear negative trends for aMED (Pnonlinear ≤ 0.035). Mediation analyses indicated that DII and CDAI accounted for 15.7%–50.4% and 15.0%–20.2%, respectively, of the association between aMED and biological age acceleration, highlighting anti-inflammatory and antioxidant mechanisms in delaying aging. Conclusion: This study provides robust evidence that dietary pro-inflammatory potential, antioxidant capacity, and Mediterranean diet adherence exhibit independent and differential associations with biological aging. Pro-inflammatory diets are associated with accelerated aging, whereas antioxidant-rich and Mediterranean diets are associated with decelerated biological aging. Mediation analyses reveal that the Mediterranean diet’s benefits are partially mediated by its anti-inflammatory and antioxidant properties. Future research should employ longitudinal designs to establish causation and clarify mechanisms, positioning diet as a key modifiable factor for healthy aging.